Impact of Land Use Change on Water Yield Using the SWAT Model in the Minraleng Sub-Watershed, Maros - Wahyullah Wahyullah; Yefane Samperuru (Jurnal Wasian, 2026)
One of the factors that influence the hydrological dynamics of a watershed is land use change, especially those related to water yield and river flow stability. The purpose of this research is to evaluate the impact of land use changes during the period 2018–2023 on water production and the River Regime Coefficient (RRC) in the Minraleng Sub-Watershed, Upper Walanae Watershed. Land cover change analysis was conducted using Sentinel-2 images from 2018 and 2023, while hydrological response was analyzed using the standard Soil and Water Assessment Tool (SWAT) model with inputs of climate, soil, topography, and land use data. Research results show that during the period 2018–2023, there was a decrease in mixed dryland agriculture, followed by an increase in secondary dryland forests and rice fields. SWAT simulations show that an increase in annual rainfall is followed by an increase in surface runoff, average discharge, and maximum discharge, while minimum discharge experiences a significant decrease. The condition of the watershed indicates that the ability to maintain base flow during the dry season has decreased. The value of the River Regime Coefficient (RRC) increased as a result of greater surface runoff, indicating an increase in river discharge variation between the rainy and dry seasons. The validation results based on community interviews show that the simulation model results are aligned. The hydrological stability of the Minraleng Sub-Watershed tends to decrease due to land-use changes and increased rainfall.